Modifikasi Pembelajaran Passing dalam Permainan Sepak Bola Menggunakan Bola Plastik di Kelas VIII SMPN 1 Cikarang Pusat - Yunus Setiawan; Aria Kusuma Yuda R; Ine Rahayu Purnamaningsih (Peneliti.net, 2021)
The purpose of this study was to determine the effect of modification using a plastic ball on soccer learning. This research is a quantitative approach research with experimental method. The population of this research is the class VIII students of SMPN 1 CIKARANG PUSAT as many as 132 students. The sample size of the study used a probability sampling technique with the type of simple random sampling. In this study, the number of samples used was 25% of the total population, namely 33 students of class VIII SMP Negeri 1 Cikarang Pusat. The design used in this research is One-Group Pretest-Posttest Design. The results of this study indicate that there is an increase in the average value before treatment (pretest) and after treatment (posttest) with data analysis using t-test obtained t value (12,000 ) > from t table (2,037) has a significant value. (0.000) < from 0.05. These results mean that there is an effect of modification using plastic balls on passing learning in soccer games. Based on the results of hypothesis testing, a significance value (0.000) < of 0.05, these results indicate that H1: accepted and H0: rejected, thus this study can be concluded that the modification of using a plastic ball has an effect on passing learning in soccer games.